PERCEIVED STRESS AND EXTROVERSION: ROLE OF GENDER - Mawra Mateen; Dr. Sara Mehmood Durrani; Dr. Saima Ambreen (International Journal of Contemporary Issues in Social Sciences, 2024)
Recent research spotlights a unique aspect whose objective is to find out the relationship between perceived stress and extroversion. The sample were University students and both genders were considered (Male and Female) to intricate gender differences among them. Sample size was comprised of 100 participants. Present research was conducted in different universities of Quetta, Balochistan. The Perceived Stress Scale containing 10 items was utilized to assess Perceived stress. Extroversion was measured using Big Five Inventory’s subscale of Extroversion containing 8 items. Correlation and independent sample t-test was used. This research concluded that perceived stress and extroversion in university students have a significant negative correlation (r = -.367**, p <0.01) and there is significant gender differences in Extroversion, males are more extroverted. These findings would be helpful in future for upcoming researchers for analyzing various psychological interrelations that are very crucial as this is need of the era to make environment as stress free regime for dwellers especially for students that are future of any nation.